THE INTEGRATION OF INFORMATION TECHNOLOGY IN ENHANCING TEACHING AND LEARNING IN RESPONSE TO COVID-19 CRISIS - Brian, Thomas (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2022)
This research aims to examines the integration of information technology into teaching and learning by examining the function of information technology and technology integration techniques in preparing students to deal with a variety of integration opportunities and barriers in the current pandemic Covid-19 situation. This paper was written with the help of literature research, literature study, and interviewing techniques. In this study, data was collected through the use of papers, online journals, digital books, and interviews. The findings reveal that existing technology has various benefits and can be used not only for entertainment, but also for proper use of existing platforms and access to all learning content without stuttering about technology. Increasing integrity of information technology leads to the modification, dissemination and creation of information innovations that have not been carried out by telematics and education professionals.